2016
DOI: 10.1089/omi.2016.0106
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Biomarkers and Neurodegeneration: A Pathway Enrichment Analysis of Alzheimer's Disease, Parkinson's Disease, and Amyotrophic Lateral Sclerosis

Abstract: Neurodegenerative diseases such as Alzheimer's disease (AD), Parkinson's disease (PD), and amyotrophic lateral sclerosis (ALS) lack robust diagnostics and prognostic biomarkers. Metabolomics is a postgenomics field that offers fresh insights for biomarkers of common complex as well as rare diseases. Using data on metabolite-disease associations published in the previous decade (2006-2016) in PubMed, ScienceDirect, Scopus, and Web of Science, we identified 101 metabolites as putative biomarkers for these three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 99 publications
4
98
0
Order By: Relevance
“…Amino acid oxidation can temporarily compensate for the decreased glucose metabolism, but eventually altered amino acid and amino acid catabolite levels likely lead to toxicities contributing to AD progression (Griffin and Bradshaw, 2016). Kori et al (2016) also found a similar pattern and proposed that alanine, aspartate, glutamate, and purine metabolism might act as alternative pathways to overcome inadequate glucose supply and energy crisis in neurodegeneration. To date, several studies have reported that cerebral brain glucose hypometabolism accurately distinguishes AD from normal aging, precedes cognitive decline and the onset of dementia among normal elderly and presymptomatic familial AD patients, and can be found in cognitively normal subjects with subjective memory complaints and in carriers of the APOE E4 genotype (Mosconi et al, 2008).…”
Section: Glucose Hypometabolismmentioning
confidence: 89%
“…Amino acid oxidation can temporarily compensate for the decreased glucose metabolism, but eventually altered amino acid and amino acid catabolite levels likely lead to toxicities contributing to AD progression (Griffin and Bradshaw, 2016). Kori et al (2016) also found a similar pattern and proposed that alanine, aspartate, glutamate, and purine metabolism might act as alternative pathways to overcome inadequate glucose supply and energy crisis in neurodegeneration. To date, several studies have reported that cerebral brain glucose hypometabolism accurately distinguishes AD from normal aging, precedes cognitive decline and the onset of dementia among normal elderly and presymptomatic familial AD patients, and can be found in cognitively normal subjects with subjective memory complaints and in carriers of the APOE E4 genotype (Mosconi et al, 2008).…”
Section: Glucose Hypometabolismmentioning
confidence: 89%
“…Common symptoms of ALS include muscle tenderness, cramping, twitching, and muscle impairment (Goetz, 2000). Later in the advance stage of the disease, patients experience dysphagia (swallowing difficulty), dysarthria (speech difficulty), and dyspnea (difficulty in breathing) (Kori et al, 2016). Environmental pollutants and diet have also been investigated for their association with ALS (Morozova et al, 2008;Yu et al, 2014).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…Respecting their structures, polyphenols are strong antioxidant, and anti-inflammatory compounds with broad contribution to manage various diseases. To date, several clinical trials were proceeded to investigate the potency of polyphenols on different NDs (Goetz, 2000;Logroscino et al, 2010;Kori et al, 2016;Morgan and Orrell, 2016;Davatgaran-Taghipour et al, 2017). Flavonoids are the major bioactive group of polyphenols with more than 6000 members ( Figure 2).…”
Section: Polyphenolsmentioning
confidence: 99%
“…Metabolomics refers to the study of quantitative data on cellular processes, molecular connections and metabolic pathways appearing in complex diseases such as neurodegenerative disorders. A recent review (Kori et al 2016 ) reported that to date 54 metabolites have been studied as biomarkers for PD. Some of these metabolites were found disease-specific and others matched also with other neurodegenerative diseases such as Alzheimer’s disease and amyotrophic lateral sclerosis.…”
Section: Omicsmentioning
confidence: 99%